Distribusi dalam Sistem Ekonomi Islam - Madnasir, Madnasir (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2011)
Distribution of economic activity in a government are very important. This is because the distribution itself became an objective of fiscal policy in a government with a form of taxation (taxes are both individual and corporate taxes). When talking about economic activity in the distribution, of course, will talk about the concept of â€œeconomyâ€ that â€œofferedâ€ by the Islamic. Looking at how Islam introduced the concept of equitable distribution of wealth of the country through the distribution, which is certainly not independent of the state revenue the teachings of Islamic Shariah, such as waris, sadaqah, zakat and waqf.